The acetyltransferase SCO0988 controls positively specialized metabolism and morphological differentiation in the model strains Streptomyces coelicolor and Streptomyces lividans - Bi, Yunwen; An, Hao; Chi, Zhewei; Xu, Zhongheng; Deng, Yuan; Ren, Yuxian; Wang, Rui; Lu, Xinyi; Guo, Jia; Hu, Ren; Virolle, Marie-Joelle; Xu, Delin (Frontiers in Microbiology, 2024)
Streptomycetes are well-known antibiotic producers possessing in their genomes numerous silent biosynthetic pathways that might direct the biosynthesis of novel bio-active specialized metabolites. It is thus of great interest to find ways to enhance the expression of these pathways to discover most needed novel antibiotics. In this study, we demonstrated that the over-expression of acetyltransferase SCO0988 up-regulated the production of specialized metabolites and accelerated sporulation of the weak antibiotic producer, Streptomyces lividans and that the deletion of this gene had opposite effects in the strong antibiotic producer, Streptomyces coelicolor. The comparative analysis of the acetylome of a S. lividans strain over-expressing sco0988 with that of the original strain revealed that SCO0988 acetylates a broad range of proteins of various pathways including BldKB/SCO5113, the extracellular solute-binding protein of an ABC-transporter involved in the up-take of a signal oligopeptide of the quorum sensing pathway. The up-take of this oligopeptide triggers the “bald cascade” that regulates positively specialized metabolism, aerial mycelium formation and sporulation in S. coelicolor. Interestingly, BldKB/SCO5113 was over-acetylated on four Lysine residues, including Lys425, upon SCO0988 over-expression. The bald phenotype of a bldKB mutant could be complemented by native bldKB but not by variant of bldKB in which the Lys425 was replaced by arginine, an amino acid that could not be acetylated or by glutamine, an amino acid that is expected to mimic acetylated lysine. Our study demonstrated that Lys425 was a critical residue for BldKB function but was inconclusive concerning the impact of acetylation of Lys425 on BldKB function.